Comparison of the corrosion behavior of pure titanium and its alloys in fluoride-containing sulfuric acid. (February 2016) - Wang, Z.B.; Hu, H.X.; Zheng, Y.G.; Ke, W.; Qiao, Y.X.
Highlights: Pd, Ni and Mo improve the corrosion resistance of titanium in solutions with fluoride. Pd and Ni can accelerate the cathodic hydrogen evolution reaction. Mo can inhibit the anodic process. Pd gets enriched while Mo and Ni get depleted on the surface. The corrosion behavior is interpreted using the mixed potential theory. Abstract: The corrosion behavior of pure titanium, Ti-0.2Pd and Ti-0.3Mo-0.8Ni alloy in fluoride-containing sulfuric acid were investigated using electrochemical methods combined with surface characterization. The results showed that titanium alloys exhibited higher corrosion resistance than pure titanium at fluoride concentrations lower than 0.002 M due to the acceleration effects of Pd and Ni on cathodic process and the inhibition effect of Mo on anodic process. But titanium alloys are still corroded as severely as pure titanium at higher fluoride concentrations. The influences of alloying elements on the corrosion behavior at different fluoride concentrations were well explained using the mixed potential theory.